If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(r + 6) = 15 Reorder the terms: 7(6 + r) = 15 (6 * 7 + r * 7) = 15 (42 + 7r) = 15 Solving 42 + 7r = 15 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + 7r = 15 + -42 Combine like terms: 42 + -42 = 0 0 + 7r = 15 + -42 7r = 15 + -42 Combine like terms: 15 + -42 = -27 7r = -27 Divide each side by '7'. r = -3.857142857 Simplifying r = -3.857142857
| -6=-4x+2-8 | | 7y-90=y-6 | | 28=12-8 | | 21=6p+9 | | 13+5z=-7 | | -3-7x-7x=-3 | | (4-i)-(5+8i)= | | 5q-8=q | | 9x-96=5x-36 | | y-x=-9x+21 | | xcosh(x/4)=1/8 | | p=2p-59 | | .25x+.7x=x-3 | | -5m=-45 | | 673.00+0.3= | | y-15=2(x-3)-17 | | B^2+6b-25=0 | | 3.5n=11 | | 8t+9=15 | | m^2-8=-11 | | 9x+25=5x-1 | | (9x+2)+23=(5x-1) | | 7x+x+(13-x)=24 | | 3x-4-4x=3x+7 | | 3(2+y)-y=4+2y+2 | | 2+3x=7+4 | | 4d+4d+d-4-3d=0 | | 20x-1=39 | | (u-4)(u+4)= | | (9x+2)=(5x-1) | | -4/9x2/3 | | -2v+9=25whats |